2011
DOI: 10.1021/jp202756s
|View full text |Cite
|
Sign up to set email alerts
|

Fulvenallene Decomposition Kinetics

Abstract: While the decomposition kinetics of the benzyl radical has been studied in depth both from the experimental and the theoretical standpoint, much less is known about the reactivity of what is likely to be its main decomposition product, fulvenallene. In this work the high temperature reactivity of fulvenallene was investigated on a Potential Energy Surface (PES) consisting of 10 wells interconnected through 11 transition states using a 1 D Master Equation (ME). Rate constants were calculated using RRKM theory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 67 publications
1
54
0
Order By: Relevance
“…As shown in Eq. (4), C 5 H 5 decomposes to acetylene and propargyl radicals at 1300 K. Likewise the fulvenallenyl radical has been observed 63,64 to decompose to propargyl radical and diacetylene. This can be summarized, 37 C 5 H 4 -C≡ ≡CH(+ M) → HCCCH 2 + HC≡ ≡C-C≡ ≡CH, The presence of the cyclopentadienyl radical and HC≡≡CH is confirmed by PIMS, PIE, and IR spectroscopy.…”
Section: A Pyrolysis Of Benzyl Radical Without Tropylmentioning
confidence: 92%
“…As shown in Eq. (4), C 5 H 5 decomposes to acetylene and propargyl radicals at 1300 K. Likewise the fulvenallenyl radical has been observed 63,64 to decompose to propargyl radical and diacetylene. This can be summarized, 37 C 5 H 4 -C≡ ≡CH(+ M) → HCCCH 2 + HC≡ ≡C-C≡ ≡CH, The presence of the cyclopentadienyl radical and HC≡≡CH is confirmed by PIMS, PIE, and IR spectroscopy.…”
Section: A Pyrolysis Of Benzyl Radical Without Tropylmentioning
confidence: 92%
“…Several test calculations showed that relative energies on the C 10 H 11 PES computed through eq 1 are comparable within 1.5 kcal/mol with those determined with CCSD(T) energies extrapolated to the CBS limit using the much more computationally expensive cc-pVDZ/cc-pVTZ extrapolation scheme we recently adopted to investigate the C 7 H 6 PES. 31,32 To improve the level of accuracy of the calculations, the energies of the saddle points whose reaction fluxes are rate determining were also calculated using the ROCBS-QB3 methodology proposed by Wood et al 33 This computational approach was designed to improve the level of accuracy of reaction energies calculated using the CBS-QB3 approach when spin contamination is relevant, thus eliminating the need to include the CBS-QB3 empirical corrections factor for spin contamination. This is accomplished by performing the calculations using spin restricted wave functions.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Density functional theory (DFT) calculations 14 found that hydrogen addition to fulvenallene would result in C 5 H 5 + C 2 H 2 . Recently, there has been extensive work [15][16][17][18][19] performed on potential energy surfaces for each of the species C 7 H 7 , C 7 H 6 , and C 7 H 5 and their interplay during benzyl radical decomposition. Because of their likely importance during the decomposition of benzyl, both fulvenallene and fulvenallenyl radicals, 20,21 as well as the cycloheptatrienyl radical 22 have been detected and identified by PIMS.…”
Section: Figmentioning
confidence: 99%